"Man is what he eats". Plant residues from dental calculus in the ancient population of Milano from Roman times to modern age. (October 2021) - Mattia, Mirko; Biehler-Gomez, Lucie; Palamenghi, Andrea; Nichetti, Deborah; Caccia, Giulia; Sguazza, Emanuela; De Angelis, Danilo; Galimberti, Paolo Maria; Fedeli, Anna Maria; Slavazzi, Fabrizio; Cattaneo, Cristina; Caccianiga, Marco
Highlights: Plant residues may be found entrapped in dental calculus of ancient skeletons. The identification of these residues can provide information on ancient diet. Major cereals were a constant finding in the varied diet of the Milanese area. Legumes partially substituted the consumption of minor cereals. This research sheds light on ancient food habits through a diachronic study. Abstract: The study of plant residues extracted from dental calculus is a potent tool for reconstructing the past. In this study, three archaeological sites of the city of Milano (Italy) from two time periods (Roman and Modern Ages) were considered. An anthropological study (biological profile and pathologies) was performed for the 150 skeletons of the study sample and when present, residues trapped in the dental calculus were extracted. Through the observation of 883 identified starch granules, the possible changes in diet over the centuries in Milano were analysed and compared with the presence of specific signs of stress markers on the skeletons. The study showed that major cereals were a constant finding in the varied diet of the Milanese area, and that over time, legumes partially substituted the consumption of minor cereals. Interestingly, no severe nutritional deficiencies nor signs of poor diet were found in the sample. This research sheds light on the food habits of the ancient inhabitants of the city of Milano through a diachronic botanical examination of dental calculus.